Feeding value of Alfalfa Leaf Protein Concentrate (ALPC) for swine - A Hsu; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1980)
Three feeding trials involving 96 starter pigs, 48 grower pigs and 48 finisher pigs were used to determine the feeding value of alfalfa leaf protein concentrate (ALPC) for swine. ALPC was substituted for 33%, 66% or 100% of dehulled soybean meal (SBM) on an equal-weight basis. Level of ALPC did not affect feed intake or feed efficiency. During the finisher phase, ALPC substituted for 66% or 100% of dehulled SBM, improved daily gain (P<.05). For the entire trial, ALPC did not affect feed efficiency; average daily gain was improved by replacing 66% dehulled SBM with ALPC (P<.05). Twelve crossbred barrows averaging 26 lb were used to determine protein and energy digestibilities and nitrogen balance in starter diets where ALPC replaced 0, 66%, or 100% of the dehulled SBM. Digestibilities of protein and energy of ALPC were 83.5% and 77.7% respectively. The digestible energy of ALPC, 4.17 kcal/g, was similar to that of dehulled SBM 4.39 kcal/g. These results suggest that ALPC can replace soybean meal in a corn diet for pigs from 17 lb to 202 lb with no adverse effects on feed efficiency, rate of gain, or carcass characteristics.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Alfalfa; Alfalfa leaf protein concentrate (ALPC); Soybean meal